Pelatihan Pemahaman Ekonomi Syariah untuk Masyarakat Desa Pomahan - Ria Kuswati; Nanik Setyowati (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The training activities were carried out in pomahan village, targeting the community of housewives weekly studi. Training activities are carried out with the aim of providing understanding to society regarding the benefits and importance of sharia economics which is carried out not only solely on profit, but economic activity can continue to grow in the future with paying attention to and implementing Islamic economics as a supporting factor. The training is customized with the problems and needs faced by the community in pomahan village. Examination method the activity consists of two stages. The first stage is the preparation of materials and permits and the second stage is the stage the implementation of the progam in the form of training includes presentation and discussion. Results and outputs after activities training is carried out, namely first, the community experiences an increased understanding of science sharia economy. With the implementation of this progam, there will be an improvement in the order of community values in economic sector, especially sharia economics